2006
DOI: 10.1007/s00335-005-0093-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bovine PRKAG3 gene: structure, polymorphism, and alternative transcripts

Abstract: The bovine PRKAG3 gene encodes the AMPK gamma3 subunit, one isoform of the regulatory gamma subunit of the AMP-activated protein kinase (AMPK). The AMPK plays a major role in the regulation of energy metabolism and mutations affecting the genes encoding the gamma subunits have been shown to influence AMPK activity. The gamma3 subunit is involved in the regulation of AMPK activity in skeletal muscle and strongly influences glycogen metabolism. Glycogen content in muscle is correlated to meat quality in livestoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
7
0
4
Order By: Relevance
“…Otra mutación que fue identificada en este mismo gen, es la denominada rn* (199I-200R) que tiene un efecto positivo sobre la CRA (Lindahl et al, 2004a y b) y mostró una elevada frecuencia alélica en poblaciones cruzadas de las razas Hampshire y Landrace utilizadas en el estudio de Enfält et al (2006). Roux et al (2006) cuando realizaron una caracterización de este mismo gen en bovinos de las razas Limousin, Charolais y Holstein identificaron 21 SNPs y al determinar las diferencias de las frecuencias alélicas por raza para cada mutación encontraron además que algunas mutaciones eran exclusivas de alguna raza, por lo que se podría considerar que estas diferencias genéticas son las responsables de variaciones en las características de calidad cárnica por raza. El segundo gen mayor es RYR, en el que se identificó la mutación R615C en porcinos, la cual incrementa las pérdidas por goteo a 24 horas PM (Otto et al, 2007).…”
Section: Los Factores Tipo Genético Madura-ción Y Su Interacciónunclassified
“…Otra mutación que fue identificada en este mismo gen, es la denominada rn* (199I-200R) que tiene un efecto positivo sobre la CRA (Lindahl et al, 2004a y b) y mostró una elevada frecuencia alélica en poblaciones cruzadas de las razas Hampshire y Landrace utilizadas en el estudio de Enfält et al (2006). Roux et al (2006) cuando realizaron una caracterización de este mismo gen en bovinos de las razas Limousin, Charolais y Holstein identificaron 21 SNPs y al determinar las diferencias de las frecuencias alélicas por raza para cada mutación encontraron además que algunas mutaciones eran exclusivas de alguna raza, por lo que se podría considerar que estas diferencias genéticas son las responsables de variaciones en las características de calidad cárnica por raza. El segundo gen mayor es RYR, en el que se identificó la mutación R615C en porcinos, la cual incrementa las pérdidas por goteo a 24 horas PM (Otto et al, 2007).…”
Section: Los Factores Tipo Genético Madura-ción Y Su Interacciónunclassified
“…Rothschild et al (2005) gained the US Patent for they found PRKAG3 alleles and use the same as genetic markers for reproductive and meat quality traits in pigs. Roux et al (2006) reported the bovine PRKAG3 gene and a polymorphism analysis in three cattle breed; 32 SNPs were identified among which 13 are in the coding region, one is in the 3' UTR and 18 are in the introns; five of them change an amino acid in the PRKAG3 protein sequence; allelic frequencies were determined in the three breeds considered, and mutant alleles affecting the coding sequence were found at a very low frequency. Similarly, Yu et al (2005) also reported that the genomic structure and sequence of the bovine PRKAG3 were analyzed from a Korean cattle BAC clone; the bovine PRKAG3 gene comprises 13 exons and spans approximately 6.8 kb on BTA2; from 5' and 3'-rapid amplification of cDNA ends experiments, the full-length cDNA of bovine PRKAG3 had been identified, encoding a deduced protein of 465 amino acids; seven single nucleotide polymorphisms were detected in four Bos taurus cattle breeds; the bovine PRKAG3 gene described in that study might be involved in muscle-related genetic diseases or meat quality traits in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive efforts are being made to control and improve these qualities but are still impaired by the fact that these characters are subjected to many genetic and environmental factors and the elucidation of the mechanisms involved requires extensive studies (Roux et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Otras investigaciones destacan la alta variabilidad de este gen, entre los que se citan a Yu et al (2005) quienes identificaron tres mutaciones funcionales y un splicing alternativo en el exón 2 y Roux et al (2006) con 32 SNPs adicionales, cinco de los cuales son funcionales. Barnes et al (2005) lograron establecer una mutación en el gen PRKAG3 humano (R225Q), que altera la deposición in vivo a nivel muscular del glicógeno, dada una pér-dida de la función de la proteína al eliminar la regulación realizada por la relación AMP:ATP, incrementando la actividad basal del AMPK.…”
Section: Discussionunclassified